Aspectos jurídicos fundamentais da gestão, controle e qualidade das decisões públicas da Lei nº 13.655/2018 - Mendes, Wallace (2021)
This research aims to analyze the application and interpretation of the standards for control, management and quality of public decisions of Law No. 13.655/2018. The research is exploratory, qualitative, in the research procedure a bibliographic and documentary survey was carried out, both in doctrine and academic works within the field of study and in consultation with related legislation and official sources. It was found that the Public Administration is bound by strict compliance with the law, observing the legality, and the State must have organs and functions that are dedicated to the inspection of administrative actions, capable of promoting corrections and amendments to violations of the legal order, requiring a methodological structure of standards and procedural means for the effective control of the acts of the Administration, for this, Law No. 13.655/2018 included ten provisions in the Law of Introduction to the Rules of Brazilian Law, set general rules for public law to improve the management and control of the Administration and brought the necessary instruments for an environment of uncertainty, establishing methodological standards to be considered in the analysis of control, increasing legal certainty in the application of norms and demanding that public decisions be examined in accordance with their complexity . Thus, through this research it was possible to analyze the application and interpretation of the rules for control, management and quality of public decisions of Law No. 13.655/2018, understanding about the legal foundations for the Control of Public Administration and the role of the State, including how efficiency and legal security contribute to the quality of public decisions that the assumptions of Law No. 13.655/2018 reflect a new existing scenario for Public Law.